2017
DOI: 10.1111/1467-9817.12111
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on orthography and phonology in reading of Chinese: A developmental study

Abstract: Background: Disruptions of reading processes due to text substitutions can measure how readers use lexical information. Methods: With eye-movement recording, children and adults viewed sentences with either identical, orthographically similar, homophonic or unrelated substitutions of the first characters in target words. To the extent that readers rely on orthographic or phonological cues, substitutions that contain such cues should cause less disruption reading than do unrelated substitutions. Results: On pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 85 publications
4
31
0
Order By: Relevance
“…Given its features, Chinese is considered as an opaque orthography since character recognition not only requires visual-sound connection but also inevitably involves the activation of the character semantics (Chen & Shu, 2001; Ho et al, 2017; Joshi et al, 2012; Zhou & Marslen-Wilson, 1999; 2000), especially with the accumulation of reading experiences (Yan et al, 2015; Zhou et al, 2018). Additionally, a large number of homophones and the semantic cues carried by the radicals for the majority of characters (DeFrancis, 1984) may contribute to the longer time needed for the mastery of character recognition.…”
Section: The Role Of Decoding and Language Comprehension In Chinese Rmentioning
confidence: 99%
“…Given its features, Chinese is considered as an opaque orthography since character recognition not only requires visual-sound connection but also inevitably involves the activation of the character semantics (Chen & Shu, 2001; Ho et al, 2017; Joshi et al, 2012; Zhou & Marslen-Wilson, 1999; 2000), especially with the accumulation of reading experiences (Yan et al, 2015; Zhou et al, 2018). Additionally, a large number of homophones and the semantic cues carried by the radicals for the majority of characters (DeFrancis, 1984) may contribute to the longer time needed for the mastery of character recognition.…”
Section: The Role Of Decoding and Language Comprehension In Chinese Rmentioning
confidence: 99%
“…One possible reason for the less robust phonological effect is that the Chinese script bears a weak form-sound relationship insofar that more time is needed for Chinese readers to activate corresponding phonological representations in the mental lexicon. Previous studies have shown that the semantic information of printed Chinese words can be more efficiently retrieved by Chinese readers (Leck et al, 1995), while phonology may play a trivial role among skilled Chinese readers because of the opaque lexical level orthography-phonology mapping (Luo et al, 2018;Zhou et al, 2018). Moreover, in a functional magnetic resonance imaging study, Brennan et al (2013) claimed that learning to read could reorganize the phonological awareness network only for alphabetic but not for logographic writing systems, which was attributed to the different principles for mapping between orthographic and phonological representations.…”
Section: Validity Of the Printed-word Vwp In Chinese Pun Researchmentioning
confidence: 99%
“…This would suggest that, in German, for children, phonology plays a more important role in word identification than orthography, whilst, for adults, the opposite pattern seems to occur: orthography seems to play a more dominant role in facilitating lexical access than phonology. In Chinese, a morphosyllabic language [48], phonological information has been shown to be activated pre-lexically by children, whilst adults seem to use more direct access from orthography to semantics [49]. Within Chinese, the researchers argued, early, pre-lexical activation of phonology diminishes as readers become more skilled.…”
Section: The Role Of Phonology: Eye Movement Researchmentioning
confidence: 99%